Potensi Kerjasama Antar Daerah Kabupaten Agam dengan Kota Bukittinggi dalam Penyediaan Air Baku - Andri Andri; Wido Prananing Tyas (Universitas Diponegoro, Indonesia, 2017)
Agam Regency and Bukittinggi city are the two neighbouring regions and administratively adjoining territory. In order to improve drinking water services, Bukittinggi city has a lack of adequate raw water sources in its jurisdiction. Most of the raw water source used by Bukittinggi city today and the potential raw water sources are in the Agam Regency. Inter-regional cooperation is considered to overcome the problems of inequality between the raw water source between two regions. This study aims to explore and determine the potential of cooperation, stakeholder support and collaboration object capacity on inter-regional cooperation between Agam Regency and Bukittinggi city in providing the raw water supply. This research is using a Quantitative Methode, selection of sampling using a Snowbowling technique. The primary data were collected through questionnaires using Guttman Scale and Likert, the analyses were performed using scoring techniques and AHP. The analysis showed that the relationship between Agam and Bukittinggi in the raw water supply was dominated by a consulting relationship and the formal cooperation has not materialized. All stakeholders strongly supportted the inter-regional cooperation between Agam and Bukittinggi in the raw water supply. The differing views were appeared in seeing the benefits and challenges of cooperation. Utilization of raw water becomes a priority in inter-regional cooperation, meanwhile the raw water service system and the legality of cooperation are the two priorities aspects in the inter-regional cooperation. The availability of raw water sources which are alocated as the object of cooperation is sufficient to meet the current drinking water needs and the 20 years projected needs to come of Bukittinggi and the population needsin sub-districts in Agam Regency adjacent to Bukittinggi.